Academy Dormitory Nearing Completion - Vallejo Times-Herald (Vallejo Times-Herald)
Work on the new $572,000 three-story dormitory for midshipmen at the California Maritime Academy is rapidly nearing the finishing stages, Capt. Henry E. Richter, USN, (Ret.) academy superintendent reported yesterday.